Occupational hand eczema reduces career length in hairdressers: a prospective cohort study of Danish hairdressers graduating from 1985 to 2007 - Havmose, Martin; Thyssen, Jacob Pontoppidan; Zachariae, Claus; Uter, Wolfgang; Johansen, Jeanne Duus (Occupational and Environmental Medicine, 2022)
Background Occupational hand eczema (OHE) is common in hairdressers, and many leave the trade because of the disease. However, the exact impact of OHE on career length is unknown. Objective To assess the effect of OHE on career length and risk factors associated with leaving the trade because of OHE in hairdressers followed-up for up to 35 years. Methods A prospective cohort study of Danish hairdressers graduating between 1985 and 2007 (n=5219) was performed. A questionnaire was sent in 2009 and 2020. The Danish Labor Marked Supplementary Pension Scheme provided information on affiliation to the hairdressing profession. Career length was assessed by Kaplan-Meier analyses. Results The median survival time was 12.0 (95% CI 11.0 to 13.0) years in graduates with OHE and 14.0 (95% CI 12.6 to 15.4) years in graduates without OHE (p<0.001). Graduates with a frequency of hand eczema (HE) of 'once', 'several times' and 'almost all the time' had a median survival time of 20.0 (95% CI 14.6 to 25.4), 12.0 (95% CI 10.7 to 13.3) and 7.0 (95% CI 5.6 to 8.4) years, respectively. Graduates with OHE that left the trade (partly) because of HE constituted 11.7% of the study population. Factors associated with leaving the trade because of HE included a history of atopic dermatitis (adjusted OR (aOR) 2.2 (95% CI 1.2 to 4.0), a history of a positive patch test (aOR 5.1 (95% CI 2.3 to 11.0) and allergy to hair dyes (aOR 9.4 (95% CI 3.4 to 25.6). Conclusion Career length is reduced in hairdressers with OHE, especially if frequently relapsing or caused by contact allergy, for example, to hair dyes.
CRIS-Team WoS Importer:2022-07-08